A Computerised Implementation of a Minimum Set of Health Indicators - Blignaut, P. J.; McDonald, T. (Methods of Information in Medicine, 1997)
Three alternative approaches to computerise primary health care services as provided in clinics in South Africa are compared. The first approach implements a system based on a head-count approach using a minimum set of indicators. This system resembles the current manual system of tally sheets. The second and third approaches implement computer systems based on patient records. The second approach is based on a very limited data set, and the third utilizes a comprehensive demographic and clinical data set. The three alternatives are compared with regard to practicality, flexibility, ease of use, accuracy and completeness of statistical reports, and time utilisation. It is concluded that the flexibility of a patientrecord approach, although more time consuming, is preferred. The second alternative is more feasible in a developing country with mostly computerilliterate nurses. Ways in which such a system can be implemented in an environment with limited hardware resources are also proposed.
Keywords: Primary Health Care; Patient Records; Tally Sheets; Data Set